Phosphate fertilization with filter cake, natural phosphate and biofertilizers in an ultisol - Caione, Gustavo; Castellanos González, Leónides; de Mello Prado, Renato [UNESP]; Reyes Hernández, Alfredo; Rosatto Moda, Leandro [UNESP]; Parets Selva, Enrique; Nahas, Ely [UNESP] (My University, 2018)
The use of biofertilizers combined with organic compost and natural sources of phosphorus may result in increased fertilizer efficiency. The aim was to evaluate the effect of the use of the filter cake with natural rock phosphate and biofertilizers on the population of microorganisms of the soil, the content of phosphorus in soil and plants and the production of dry matter of corn crop. The experiment was developed at greenhouse, using corn DKB 390 VTPRO II cultivar, sowed in pots of 5 dm3 containing Ultisol. Seven treatments were evaluated: only the soil; soil with phosphate rock (PR); filter cake; PR with filter cake; PR with filter cake and Biopack Sc®; PR with filter cake and Embrafós: FF organic Plus® and PR with filter cake and Azotofos. The experimental design was completely randomized, with three repetitions. The height, diameter of the stem, number of leaves and dry biomass of the plants, and the populations of microorganisms were determined, the content of phosphorus in soil and plants was also determined. The soils with filter cake, natural phosphate and biofertilizers presented higher population of total bacteria; however, they did not increase the mass dries, the phosphorus concentration in the soil and accumulation of phosphorus in the aerial part of the plants when compared only to the use of filter cake and natural phosphate. The filter cake in the fertilization promoted higher phosphorus content in the soil and accumulation for the plants, higher growth of the plants and microbial population in the soil, in relation to the treatments with filter cake absence.
Adubação fosfatada com torta de filtro, fosfato natural e biofertilizantes em ultisol (Argissolo)
Keywords: Microorganisms; Organomineral fertilization; Phosphorus; Zea mays